Diagnosing axial spondyloarthritis by multidiciplinary team conference at 3.5 years' follow-up in a cohort of patients with disease features according to the ASAS criteria. (4th July 2022) - Kiil, RM; Mistegaard, CE; Jurik, AG; Christiansen, AA; Hendricks, O; Schiøttz-Christensen, B; Loft, AG
Abstract : Objectives: During the past two decades, magnetic resonance imaging (MRI) has increasingly been used diagnostically in axial spondyloarthritis (axSpA), and in 2009 MRI was introduced in the Assessment of SpondyloArthritis Society (ASAS) classification criteria. In clinical practice, there is a risk of overdiagnosis if MRI findings are not related to clinical and biochemical findings. The aim of this study was to provide an estimate of the prevalence of axSpA in a cohort of clinical patients with low back pain and findings suggestive of axSpA according to ASAS through consensus diagnosis at a multi-disciplinary team (MDT) conference, and to describe the performance of the features included in the ASAS criteria. Method: Consensus diagnoses of axSpA at MDT conferences were retrospectively established at 3.5 years' follow-up in a cohort of 84 patients, initially referred with disease features according to the ASAS criteria. Patients were examined clinically regarding spondyloarthritis features, and biochemical tests and MRI of the sacroiliac joints and entire spine were performed at baseline and after a mean of 3.5 years. Results: According to the MDT consensus, 25 patients (30%) of the total cohort had axSpA at follow-up; 40% of individuals who fulfilled the ASAS criteria at baseline had axSpA, and 37% at follow-up; 96% of axSpA patients according to the MDT consensus met the ASAS criteria at baseline and 92% at follow-up. Conclusion: Approximately one-third of the included patients had axSpA when evaluated at the MDT conference. The ASAS criteria had low predictive value, but high sensitivity at both baseline and follow-up.